High Commitment Human Resource Management Practices and Employee Outcomes, HR Attribution Theory and a Proposed Model in the Context of Bangladesh - Rimi, Nadia Newaz (Information Management and Business Review, 2013)
Human resource management (HRM) practices have been studied as a composite or bundle approach with different names including different practices. Each bundle includes common HRM practices of staffing, compensation, training and development, performance appraisal, job design and career development issues with varying dimensions. The present study refers these HRM practices as High Commitment HRM (HCHRM) practices. Prior studies identify these HCHRM practices related to employee outcomes of satisfaction, commitment and retention. Consistent with early findings, the present study believes a relation between HCHRM and employee outcomes. Additionally, HR attribution theory is discussed here to explain the causal relationship between HCHRM practices and employee outcomes. Based on the review of HCHRM practices literatures and existing HRM practices of Bangladesh, a research model is proposed and propositions are developed, The model is expected to be tested in future to identify the relationship among HCHRM practices, HR attribution and employee outcomes in the context of Bangladesh. The proposed model can be tested in other countries as well.